2019
DOI: 10.1002/jee.20289
|View full text |Cite
|
Sign up to set email alerts
|

Elementary teachers' perceptions of K‐5 engineering education and perceived barriers to implementation

Abstract: Background The Next Generation Science Standards (NGSS) call for the integration of engineering content and practices in elementary science curricula, yet little is known about elementary teachers' preparedness to do so or their views on teaching engineering. Purpose/Hypothesis The purpose of the current study was to explore K‐5 teachers' perceptions about incorporating engineering in their classrooms as well as the perceived barriers for doing so. Design/Method This study consisted of an online survey includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 23 publications
6
19
1
Order By: Relevance
“…Also of note was the significant increase in participants’ EDSI scores. The authors are unaware of prior studies examining changes in EDSI scores for K‐12 teachers, however, the preassessment EDSI scores for this study are consistent with previously reported EDSI scores for K‐5 teachers (Hammack & Ivey 2017, 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Also of note was the significant increase in participants’ EDSI scores. The authors are unaware of prior studies examining changes in EDSI scores for K‐12 teachers, however, the preassessment EDSI scores for this study are consistent with previously reported EDSI scores for K‐5 teachers (Hammack & Ivey 2017, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Initially, TEAMS participants reported lack of time for teacher learning, lack of teacher training, and lack of teacher knowledge to be significant barriers to implementing engineering, which is consistent with previous work (Hammack & Ivey 2017, 2019). Further, many of the reported barriers decreased over the course of TEAMS, though we lacked the power to detect significance.…”
Section: Discussionsupporting
confidence: 81%
“…In fact, Cunningham, Lachapelle, and Lindgren‐Streicher () found that elementary teachers have an overly broad idea of what engineers do and confuse the work of engineers with that of construction workers, electricians, and automotive mechanics. Further, in a statewide survey of elementary teachers, Hammack () found that some elementary teachers hold a misconception of engineering as being extremely difficult and only appropriate for advanced students. Additionally, Knezek, Christensen, and Tyler‐Wood () found that the STEM perceptions of preservice elementary teachers were not significantly different from middle school students’ perceptions.…”
Section: Related Literaturementioning
confidence: 99%
“…Despite some successful efforts, formal mechanisms for change are still varied or deficient (National Academy of Engineering [NAE] and National Research Council [NRC], 2014). While we will need well‐prepared educators to address new learning outcomes, teachers are already overworked (Scholastic and the Bill and Melinda Gates Foundation, 2012), and researchers position them as underprepared to meet these challenges (Antink‐Meyer & Meyer, 2016; Hammack & Ivey, 2019; Judson et al, 2016). We argue that partnerships among school systems, engineers, and researchers may help alleviate issues of teacher preparedness, while supporting overburdened schools in addressing national STEM workforce development objectives.…”
Section: Introductionmentioning
confidence: 99%